2022
DOI: 10.1038/s41598-022-07310-4
|View full text |Cite|
|
Sign up to set email alerts
|

On the intensity decay of tropical cyclones before landfall

Abstract: It remains unclear how tropical cyclones (TCs) decay from their ocean lifetime maximum intensity (LMI) to landfall intensity (LI), yet this stage is of fundamental importance governing the socio-economic impact of TCs. Here we show that TCs decay on average by 25% from LMI to LI. A logistic decay model of energy production by ocean enthalpy input and surface dissipation by frictional drag, can physically connect the LMI to LI. The logistic model fits the observed intensity decay as well as an empirically expon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The lifetime maximum intensity (LMI) of a TC is the intensity closest to its theoretical upper limit and has received much more attention than the intensity in any other period of its lifecycle. However, the location of LMI is usually hundreds of kilometres away from land 7 , and an intensity decay from the LMI to LI frequently occur before landfall 8 . The long-term TC socio-economic impact is ultimately driven by the number of intense storms making landfall.…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime maximum intensity (LMI) of a TC is the intensity closest to its theoretical upper limit and has received much more attention than the intensity in any other period of its lifecycle. However, the location of LMI is usually hundreds of kilometres away from land 7 , and an intensity decay from the LMI to LI frequently occur before landfall 8 . The long-term TC socio-economic impact is ultimately driven by the number of intense storms making landfall.…”
Section: Introductionmentioning
confidence: 99%
“…This can also be seen in the energy balance approaches. For example, the wind speed tendency equation of Wang and Toumi (2022b) also points to a possible universal balance of heating and dissipation with either being dominant reversing the sign. The similar correlation between the central pressure change and reciprocal size for both decaying and intensifying TCs suggests that the geometric core size effect is one of the fundamental properties controlling rates of intensity change.…”
Section: Discussionmentioning
confidence: 99%
“…Montgomery et al. (2001) and Wang and Toumi (2022b) propose turbulent frictional decay as an important driver, but the effect of size is not considered.…”
Section: Introductionmentioning
confidence: 99%
“…• Distance to land (DTL) DTL is also an important predictor, and the intensity of TC diminishes significantly after landfall, which is well reflected in the SHAP values. The study showed that, the intensity of TCs is affected by their distance from land [45,53]. Generally, the further away a cyclone is from land, the more intense it can become.…”
Section: Explainable Analysismentioning
confidence: 98%